A Prediction Method for Acoustic Intensity Vector Field of Elastic Structure in Shallow Water Waveguide. (19th October 2020) - Wang, Wenbo; Yang, Desen; Shi, Jie
Abstract : Compared with scalar sound field, vector sound field explained the spatial structure of sound field better since it not only presents the sound energy distribution but also describes the sound energy flow characteristics. Particularly, with more complicated interaction among different wavefronts, the vector sound field characteristics of an elastic structure in a shallow water waveguide are worthy of studying. However, there is no reliable prediction method for the vector sound field of an elastic structure with a high efficiency in a shallow water waveguide. To solve the problem, transfer functions in the waveguide have been modified with some approximations to apply for the vector sound field prediction of elastic structures in shallow water waveguides. The method is based on the combined wave superposition method (CWSM), which has been proved to be efficient for predicting scalar sound field. The rationality of the approximations is validated with simulations. Characteristics of the complex acoustic intensity, especially the vertical components are observed. The results show that, with constructive and destructive interferences in the depth direction, there could be quantities of crests and vortices in the spatial structure of time-dependent complex intensity, which manifest a unique dynamic characteristic of sound energy. With more complicated interactions among the wavefronts, a structure source could not be equivalent to a point source in most instances. The vector sound field characteristics of the two sources could be entirely different, even though the scalar sound field characteristics are similar. Meanwhile, source types, source parameters, ocean environment parameters, and geo parameters may have influence on the vector sound field characteristics, which could be explained with the normal mode theory.